(untitled) (Eurasian Journal of Ecology, 2016)
In the article shows data by recovery Ural-caspian populations of Alosa kessleri kessleri. Spawning migrations of species in the river Ural not registered several ten years. In 2009-2011 in this river become apparent spawning herd. In 2009 spawning fishes were at 3+. The next two years spawning fishes were at 4+ and 5+. That would indicate about recovery field populations.